Review Essay: Educational Perspectives on the Encyclopedia of Disability, in Three Parts - Jordan, Kathy-Anne; Oppenheim, Rachel; Wong, Jean Y.; Snow, Carrie (Disability Studies Quarterly, 2006)
No abstract available